A bibliography of the finds in the desert of Judah 1970-1995 : arranged by author with citation and subject indexes - García Martínez, Florentino. (Studies on the Texts of the Desert of Judah, 1996)
This volume contains a bibliography of the research on the Dead Sea Scrolls published during the last 25 years, and as such it provides scholars with an indispensable tool for further research. Although originally planned as a continuation of B. Jongeling's A Classified Bibliography of the Finds of the Desert of Judah 1958-1969 , the materials are presented in a different way in order to avoid unnecessary duplications of entries. Each bibliographical entry is alphabetically listed in the first part of the book and is provided with an identification number which allows for multiple classifications. The second part offers a sophisticated classification of the materials by themes, topics and key words, but also by manuscript numbers and titles of the compositions as well as by authors.